SQM/COSMO Scoring Function: Reliable Quantum-Mechanical Tool for Sampling and Ranking in Structure-Based Drug Design - Pecina, Adam; Eyrilmez, Saltuk M; Köprülüoğlu, Cemal; Miriyala, Vijay Madhav; Lepšík, Martin; Fanfrlík, Jindřich; Řezáč, Jan; Hobza, Pavel (ChemPlusChem, 2020)
Quantum mechanical (QM) methods have been gaining importance in structure-based drug design where a reliable description of protein-ligand interactions is of utmost significance. However, strategies i. e. QM/MM, fragmentation or semiempirical (SQM) methods had to be pursued to overcome the unfavorable scaling of QM methods. Various SQM-based approaches have significantly contributed to the accuracy of docking and improvement of lead compounds. Parametrizations of SQM and implicit solvent methods in our laboratory have been instrumental to obtain a reliable SQM-based scoring function. The experience gained in its application for activity ranking of ligands binding to tens of protein targets resulted in setting up a faster SQM/COSMO scoring approach, which outperforms standard scoring methods in native pose identification for two dozen protein targets with ten thousand poses. Recently, SQM/COSMO was effectively applied in a proof-of-concept study of enrichment in virtual screening. Due to its superior performance, feasibility and chemical generality, we propose the SQM/COSMO approach as an efficient tool in structure-based drug design.
Keywords: in silico drug design; molekulární struktura; Drug Design; Molecular Structure; protein-ligand binding; racionální návrh léčiv; proteiny; Ligands; virtual screening; Quantum Theory; semiempirical methods; kvantová teorie; ligandy; Proteins; quantum mechanics